Imbalance in PB IL-17-Secreting and Regulatory Cells in Pars Planitis Is Associated with Dysregulation of IFN-γ-Secreting Cells, Especially in Patients with Clinical Complications. (31st July 2020) - Kosmaczewska, Agata; Przeździecka-Dołyk, Joanna; Turno-Kręcicka, Anna; Ciszak, Lidia; Szteblich, Aleksandra; Węgrzyn, Agnieszka; Frydecka, Irena; Misiuk-Hojło, Marta
Abstract : Background/Purpose . Pars planitis (PP) is a chronic intermediate uveitis of undefined cause, although autoimmune etiology is strongly suggested. This study was undertaken to evaluate circulating pro- and anti-inflammatory lymphocyte subpopulations in patients with PP. A better understanding of immune alterations in PP may contribute to the development of an appropriate biologic treatment approach. Material and Methods . In our case-control study, samples of peripheral blood from 15 patients with pars planitis and 17 healthy subjects were collected. The patients underwent a full ophthalmological evaluation including macular optical coherence tomography (OCT) and submacular choroid (with enhanced deep imaging) with the SD-OCT Spectralis system. By flow cytometry, we assessed lymphocyte subpopulations as follows: Th1 subset: CD3+CD8-IFN- γ + and CCR4-CXCR3+IFN- γ + cells, Th17 subset: CD3+CD8-IL-17+ and CCR4+CCR6+IL-17+ cells, T regulatory (Treg): CD4+CD25hiCD127- cells, T suppressor (Tsup): CD8+CD28-FOXP3+ cells, and B regulatory (Breg): CD19+CD24hiCD38hi cells. The results are presented as the median percentage of immune cells in comparison to those obtained from the healthy control group. Results . In patients, an increase in the population of Th17-secreting cells negatively correlated with the abundance of both IFN- γ -producing and T regulatory as well as suppressor cells, regarding all the phenotypes studied. Although a strong dependence of the PB Th1 cell compartment on the duration of the disease was observed, it was limited to the subgroup of patients with macular edema only. The frequency of B regulatory cells was unchanged compared to controls. Conclusions . In pars planitis, the alterations in lymphocyte cell distribution affect primarily the T cell repertoire. The imbalance in PB Th1/Th17/Treg cells creates proinflammatory conditions, strengthening the suggestion that the immune background may play a role in pars planitis pathogenesis. Also, circulating Th1 level may be of potential clinical relevance in terms of prediction of a more severe course of the disease.